The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1415-43662012000900014
|View full text |Cite
|
Sign up to set email alerts
|

Termorregulação e desempenho de tourinhos Sindi e Guzerá, no agreste paraibano

Abstract: R ESU M ONeste trabalho objetivou-se avaliar os índices bioclimáticos que influenciam as varáveis fisiológicas, desempenho e consumo de nutrientes de tourinhos das raças Gir e Guzerá. O estudo foi realizado na Estação Experimental de Alagoinha/EMEPA-PB, no município de Alagoinha, no agreste paraibano, Brasil, utilizando-se 16 tourinhos das raças Sindi e Guzerá (8 animais de cada raça), com média de 31,5 ± 1,5 meses de idade, mantidos confinados. O delineamento estatístico utilizado foi o de blocos inteiramente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
1
8
0
3
Order By: Relevance
“…In Table 2 it can be observed that in the morning and afternoon periods (P> 0.05), the air temperature averages presented high values, out of the range recommended for zebuines of 10 to 27 ºC (FURTADO et al, 2012). Relative humidity was below 40%; however, in the night and in dawn periods (P> 0.05), the mean was higher than 70%; however, in the literature, the relative humidity is recommended between 40 and 70% for most of the domestic species (NÄÄS and ARCARO JÚNIOR, 2011).…”
Section: Resultsmentioning
confidence: 95%
“…In Table 2 it can be observed that in the morning and afternoon periods (P> 0.05), the air temperature averages presented high values, out of the range recommended for zebuines of 10 to 27 ºC (FURTADO et al, 2012). Relative humidity was below 40%; however, in the night and in dawn periods (P> 0.05), the mean was higher than 70%; however, in the literature, the relative humidity is recommended between 40 and 70% for most of the domestic species (NÄÄS and ARCARO JÚNIOR, 2011).…”
Section: Resultsmentioning
confidence: 95%
“…The animal performance is also determined by the intake of nutrients, their digestibility, and metabolism, which are related to the dry matter intake, which in turn can be greatly influenced by climatic elements (FURTADO et al, 2012). As the ambient temperature is increased, dry matter intake is reduced to reduce the heat increment and control body temperature, since the animal will be more prone to heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…Avaliando a temperatura do ar, esta caracterizou-se fora da zona de conforto térmico (ZCT) para bovinos, que estabelecem uma faixa de 16 a 28ºC para bovinos indianos. Fornecer aos animais um ambiente de criação dentro da ZCT é essencial na produção animal, já que eles têm gasto mínimo de energia para mantença, maximizando o crescimento e, consequentemente, o seu potencial produtivo (FURTADO et al, 2012 Analisando o índice de temperatura de globo e umidade (ITGU) percebe-se que os maiores valores encontram-se durante a tarde, podendo-se relatar uma amplitude de 6,4°C, caracterizando o ambiente com situação de emergência havendo a necessidade iminente de provimento de instalações que modifiquem essa situação e promovam um ambiente que proporcione conforto aos animais e consequentemente estes possam expressar seu máximo potencial produtivo.…”
Section: Resultsunclassified